Stimulation by glucocorticoids of protein degradation in hepatocyte monolayers. - Hopgood, M F (1981)
1. Protein degradation in rat hepatocytes in stationary monolayer culture was measured as release of radioactive trichloroacetic acid-soluble material from intracellular proteins labelled with [3H]leucine. 2. Glucocorticoids, but not other steroids, stimulated protein breakdown in the hepatocyte monolayers. The effects observed were greater when the cells were preincubated with the hormones, indicating that the stimulation was not immediate. In addition, the stimulation by glucocorticoids persisted for up to 4 h after hormone removal. 3. Cycloheximide and the lysosomotropic agents leupeptin and ammonia effectively blocked glucocorticoid stimulation of protein degradation. 4. Insulin blocked dexamethasone stimulation when added at the same time as the steroid, but not when added 3 h later. 5. Stimulation of protein breakdown by dexamethasone was additive with that by glucagon or dibutyryl cyclic AMP, suggesting that its mechanism of action is different from that of the latter two agents. 6. Total activities of several lysosomal enzymes were unaffected under conditions where protein breakdown was stimulated by either glucagon or dexamethasone. 7. It is suggested that, whereas glucagon, dibutyryl cyclic AMP and insulin modulate protein breakdown in these cells via changes in autophagocytosis, the stimulation by glucocorticoids is exerted independently, perhaps by stimulating the synthesis of membrane proteins essential to the autophagic process.